Holding Power of 3.5 mm Versus 4.0 mm Screw Applications Placed in Stripped 2.7 mm Screw Sites - Fitch, R. B.; Kerwin, S. C.; Sedrish, S. A.; Hosgood, G.; Oliver, J. L.; Kelly, K. (Veterinary and Comparative Orthopaedics and Traumatology, 1998)
Mechanical stripping of orthopaedic screws is a complication that can occur during plate fixation of fractures. This report compares the holding power of 3.5 mm cortical and 4.0 mm cancellous orthopaedic screws inserted as a salvage technique in stripped 2.7 mm screw sites in cadaver bone. Both 3.5 mm and 4.0 mm orthopaedic screws were applied with and without tapping to stripped screw sites in the diaphysis of mature canine tibiae. Mechanical testing of the pull-out force required to extract these screws showed that all of the applications have comparative holding powers, but the 4.0 mm screw had significantly greater holding power when compared with the 3.5 mm screw. Tapping the stripped screw site, prior to placing the 3.5 mm or 4.0 mm screw, did not significantly affect the holding power. The 4.0 mm cancellous screw has the advantages of significantly greater holding power and less interference with the 2.7 mm dynamic compression plate, when compared to the 3.5 mm cortical screw.The holding power of 3.5 mm cortical and 4.0 mm cancellous orthopaedic screws placed tapped and untapped into 2.7 mm stripped screw sites in post-mortem canine tibiae were compared. All applications had comparable holding power, but with the 4.0 mm screw the holding power was significantly greater. Tapping stripped screw sites did not have any significant effect on holding power.
Keywords: Canine; screws; holding power; screw stripping; fracture repair